NASICON Electrodes: A Low‐Temperature Sodium‐Ion Full Battery: Superb Kinetics and Cycling Stability (Adv. Funct. Mater. 11/2021). (10th March 2021) - Rui, Xianhong; Zhang, Xianghua; Xu, Shitan; Tan, Huiteng; Jiang, Yu; Gan, Li Yong; Feng, Yuezhan; Li, Cheng Chao; Yu, Yan
Abstract : In article number 2009458, Cheng Chao Li, Yan Yu, and co‐workers develop a superior low‐temperature sodium‐ion battery composed of 3D porous Na3 V2 (PO4 )3 /C and NaTi2 (PO4 )3 /C foams. Benefiting from the superiority of NASICON electrodes and 3D interconnected porous structures, the designed full cell demonstrates fast kinetics and cycling stability (20 C) at −20 °C.